The ability to extrapolation formation as the condition for sportsmanship improvement in volleyball - Kochurova, L. A.; Avramova, N. V.; Burtsev, A. V. (The Russian Journal of Physical Education and Sport, 2016)
Annotation. The search for the new ways of sports training system development, on the basis of a deeper study of kinesiological potential, gives a trainer an opportunity to use different approaches to the training lessons organization. Volleyball is a highly dynamic kind of sport and it has high demands to the variability of the structural content of a motor act because of constant new situations in a game, which demand the mastered technique fulfillment with considerable changes of its parameters: direction of movement, speed of movement, power and the flight trajectory of a ball and others. It is connected with the necessity to change the conditions of the mastered earlier technique fulfillment. New forms of motional actions construction is realized more successfully in case of motional skill formation. Materials. One of the factors, which determine technical-tactical readiness of a volleyball player, is motional actions extrapolation, new skills formation on the basis of mastered earlier. This phenomenon is based on the use of the main structure of the studied motional action as a necessary condition for its fulfillment in the system of one-type in structure exercises, but in another situation. Such kind of variability of a motional action is connected with the change of conditioned- reflexive connections during new motional skills formation. Research methods: scientific-methodical literature analysis and summarizing, pedagogical experiment, testing, statistical data processing. Results. The level of technical-tactical readiness increase among female volleyball players is connected with a repeated fulfillment of motional actions with the same structure, which decreases the level of working capacity, emotional state of the training lessons, conditions faster tiredness. The methodology is created, which provides the mechanism of extrapolation development on the basis of the range of preparatory exercises broadening in volleyball. Its effectiveness is checked experimentally. Conclusion. The results of pedagogical experiment showed, that extrapolation of sports activity of a volleyball player is an important factor, which provides the level of physical and technical-tactical readiness increase. The diversity of muscular load increases the interest concerning educational-training process, optimizes psycho-emotional state of sportsmen.